Fermentable sugars from agrowastes using cellulase enzymes from local white rot fungi pycnoporus sanguineus - Norhazmiza Ahmad Safri; Rafidah Jalil; Mohd. Sahaid Kalil (Penerbit Universiti Kebangsaan Malaysia, 2017)
The viability of fermentation process is very much depends on the use of a cheap carbon source from lignocellulosic materials. It needs to hydrolyse into simple and readily metabolize carbohydrate using cellulase enzyme. Pycnoporus sanguineus has been able to produce cellulase enzyme with high enzyme activity that can convert lignocellulosic materials into fermentable sugar. P. sanguineus was culture using α-cellulose as carbon source for enzyme production via submerged fermentation (SMF) at different agitation speeds (100 and 150 rpm). Crude cellulase enzyme extracted from fermentation broth by centrifugation was used in hydrolysis of sawdust and sugarcane bagasse at different substrate concentrations (1-5% w/v). It was found that crude cellulase enzyme contain three main enzymes components i.e. endoglucanase, exoglucanase and xylanase with maximum activity of 1.55, 0.45 and 8.0 U/mL respectively that achieved after four days of cultivation at agitation speed of 150 rpm. The most suitable temperature and substrate concentration for sawdust and sugarcane bagasse hydrolysis by cellulase from P. sanguineus was at 30°C and 5% (w/v) where sugarcane bagasse produced maximum of 59.10 g/L fermentable sugar as compared to from sawdust (58.84 g/L). Fermentable sugar productivity was the highest (2.45 g/L/h) when sawdust was use compared to 0.50 g/L/h for sugarcane bagasse. Fermentable sugar produced from agrowastes using cellulase enzymes of P. sanguineus has highest potential as a feedstock for biofuels and biochemicals production.